Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
lam Nguyễn

Cho M = -20

M = ( m - b + 11 ) - ( -m - b + 15 ) - m

Phan Mỹ Quân
23 tháng 1 2018 lúc 22:28

Ta có : (m-b+11)-(-m-b+15)-m=-20

       => m-b+11+m+b-15-m=-20

       => m+m-m+b-b+11-15=-20

      => m+(-4)=-20

      => m= -20+4

      => m= -16

Chúc bạn học giỏi 

Đừng quên nhé ! ^-^

Phong Phùng
23 tháng 1 2018 lúc 22:17

Vì M= -20

=>-20 = (m-b+11)-(-m-b+15)-m

=> -20=m-b+11+m+b-15-m

=> -(m-b+11+m+b-15-m)=20

=> -m+b-11-m-b+15+m=20

=> -m+b-m-b+m=20+11-15

=> m-m+b-b+m = 16

=> m=16

Vậy m=16


Các câu hỏi tương tự
48. Hồ Tiến Vương 6/12
Xem chi tiết
ỵyjfdfj
Xem chi tiết
SHIBUKI RAN
Xem chi tiết
linh yoonmin
Xem chi tiết
ỵyjfdfj
Xem chi tiết
chi
Xem chi tiết
Nguyễn Thị Thanh Hằng
Xem chi tiết
Pham Trong Bach
Xem chi tiết
Nguyễn Thị Quỳnh Tiên
Xem chi tiết